Teacher participation in community development in the Insikazi Circuit in Mpumalanga Province - Maseko, Thandi Eunice (My University, 2013)
This study was undertaken with the purpose of investigating the involvement of educators in community development in the lnsikazi Circuit. In terms of research design, the study used a case study, namely the lnsikazi community. In-depth interviews were carried out with participants. Focus group discussions were also used to weigh the different standpoints of stakeholders and establish areas of agreement and disagreement. In line with the dictates of qualitative research, data analysis was done using the constant comparative method. Each interview was transcribed, labelled and appropriately coded using emerging themes. The researcher found that educators should act as promoters of community education by inviting the community to school meetings and sensitizing them about the need for their children's' education. However educators do not get the opportunity to do so since the majority of parents do not honor such meetings. Some of the key findings include: • Educators were seen as sources of information for the community by bringing awareness to the community but their busy schedules usually mitigate against their playing this role. • Educators should be community mobilizers but they are not effective in this role as they are usually out of touch with community needs. • Educators should play the role of as organizers and coordinators of the different stakeholders, but the majority of them indicated that they were not interested in community work as it is demanding. Some of the reasons that hampered effective educator participation in community development include a lack of time, unresponsive parents/community and lack of monetary incentives. It is therefore recommended that to overcome all these problems there needs to be regular interaction between the community and the educators. During such interactions, issues pertaining to community development and how community development should benefit both the community and the educators should be highlighted. It is the researcher's hope that through such interactions, it will be possible to build genuine partnerships between the community, educators and other stakeholders.
Thesis ( M.Dev.) -- University of Limpopo, 2013
Keywords: Involvement of teachers; Community development; lnsikazi Circuit; Teachers and community; Teachers -- Out-of-school -- Activities